Minimum wages in the apprenticeship market : adverse effects on labor demand? - Langen, Henrika [Verfasser]; Dörsam, Michael [Verfasser] (My University, 2025)
“To increase the attractiveness of vocational education and training and secure a sufficient supply of skilled labor, the German government introduced a statutory minimum wage for apprenticeship contracts. As of January 1, 2020, apprentices starting an apprenticeship that year became entitled to an annually increasing minimum wage. Merging apprenticeship posting data from the Federal Employment Agency with ad- ministrative data on apprenticeship contracts, we investigate the causal effect of this minimum wage legislation on labor demand. Exploiting regional and occupational variation in the share of apprenticeships paid at the minimum wage level, we estimate a standard difference-in-differences, a triple difference, and a synthetic difference-in-differences model. Our estimates suggest that the introduction of the minimum wage had no significant effect on the overall number of apprenticeship postings in low-wage occupations in districts with a high prevalence of minimum wage contracts. However, when examining the minimum wage effect in selected low-wage occupations separately, we find substantial differences with no observable impact on health and wellness apprenticeships but a substantial reduction in apprenticeship postings in various low-wage production and manufacturing occupations.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 2.1.6 Arbeits- & Tarifrecht; S 6 Berufsbereiche; 370; Ausbildungsstellenmarkt; Ausbildungsvergütung; Mindestlohn; Rechtliche Regelungen; Auswirkung; Berufsbereiche